THU0245 Post-Vaccinal Arthritis in an Ebola Vaccine Trial with a Live-Attenuated Recombinant Virus Expressing the Ebola Surface Glycoprotein (RVSV-ZEBOV). (9th June 2015) - Finckh, A.; Yerly, S.; Dayer, J.-A.; Huttner, A.; Lazarou, I.; Fabreguet, I.; Berner, J.; Tapparel, L.; Kaiser, L.; Gabay, C.; Siegrist, C.-A.
Abstract : Background: The recent ebolavirus outbreak is a global public health concern, warranting the development of safe and effective vaccines. A live-attenuated recombinant vesicular stomatitis virus expressing the Ebola virus surface glucoprotein (rVSV-ZEBOV) is one of the promising candidate vaccines. Under the coordination of the World Health Organization, the VSV-Ebola Consortium initiated a trial to assess the safety of various doses of rVSV-ZEBOV. Objectives: To describe rheumatic adverse events following rVSV-ZEBOV vaccination. Methods: Investigator-driven phase I/II, dose-finding, placebo-controlled, double blind trial of rVSV-ZEBOV at 10 7 or 5x10 7 pfu or placebo. Subjects with incident rheumatic symptoms were referred to a rheumatologist for a standardized workup including imaging. Results: 59 subjects received either rVSV-ZEBOV (n=51) or placebo (n=8). Baseline characteristics did not differ among treatment groups. Mild to moderate early-onset reactogenicity was frequent (50/51 vaccinees, 98%), with early low grade fevers, headaches and myalgias that vanished promptly (median 1 day). Low-level rVSV RNA was detected in plasma only on days 1 and 3. Unexpectedly, 11/59 subjects (19%) experienced acute inflammatory arthralgias at a median of 11 days after vaccination (IQR: 9 – 13). Eight presented with asymmetrical and migratory involvement of peripheral joints (median 2.5 (range 1-4)), and three with axial disease. Synovitis and tenosynovitis could be confirmed by ultrasound in 7/8 subjects with peripheral arthritis and MRI demonstrated an interspinal bursitis in 1/3 subjects with axial involvement. Acute-phase reactants were not elevated, HLA B-27 prevalence was not increased (10%), and no elevation in auto-antibodies was observed. Arthralgias were self-limited, lasting on average 11 days (IQR: 8-18). Functional impact was moderate (median RAPID3 score: 2.5, IQR: 1.8-3.3) and disease activity low (median DAS44: 1.8, IQR: 1.7-2.0). Three vaccinees also experienced a diffuse maculo-papular skin rash with small vesicles. rVSV RNA was detected in the synovial fluid (1*) and in skin vesicles (3*), but no replication of the virus could be demonstrated in the synovial fluid. Occurrence of arthritis was associated with decreased drop in lymphocyte counts at day 1 (p=0.033). All patients responded well to a limited course of NSAIDs or a single infiltration with glucocorticoids. Conclusions: The occurrence of arthritis following a symptom-free interval was unexpected and lead to a temporary suspension of the trial. Detection of rVSV RNA in the synovial fluid suggests the presence of rVSV-ZEBOV in affected joints, as reported following rubella infection or vaccination. However, no replication of rVSV-ZEBOV could be demonstrated. The most likely hypothesis is thus that rVSV-ZEBOV-induced arthritis is associated with immune-complex deposition. Disclosure of Interest: None declared